Work motivation and psychological Well-Being of volunteers and non-volunteers: Motivación laboral y bienestar psicológico de voluntarios y no voluntarios. - Karla Gastañaduy, Dora Herrera, Willy Lens, (Revista de Orientación Educacional, 2019)
Abstract: This study aims to describe similarities and differences in the motivational profile and psychological well-being between two groups of 94 paid employees each, one of them are volunteering fire fighters, the others are non-volunteers. The scales of Motivation at Work (Gagné, et al., 2010, 2012) and Psychological Well-being (Ryff, 1989) were used. Results have shown that the non-volunteers scored significantly higher for external behavioral regulation/motivation and introjected motivation. Identified and intrinsic motivation was significantly higher in the group of volunteers. If behavior regulators are categorized in autonomous and controlled motivation, it is clear that in both groups autonomous work motivation is significantly higher tan controlled motivation. As expected, based on Self-determination theory (Deci & Ryan, 2000), volunteers had a significantly higher score for autonomous motivation and a significantly lower score for controlled motivation. Although well-being correlated positively with autonomous motivation, no significant mean differences were found between the two groups.